2017
DOI: 10.1021/acs.analchem.7b02450
|View full text |Cite
|
Sign up to set email alerts
|

“From the Edge to the Center”: Viscoelastic Migration of Particles and Cells in a Strongly Shear-Thinning Liquid Flowing in a Microchannel

Abstract: Controlling the fate of particles and cells in microfluidic devices is critical in many biomedical applications, such as particle and cell alignment and separation. Recently, viscoelastic polymer solutions have been successfully used to promote transversal migration of particles and cells toward fixed positions in straight microchannels. When inertia is negligible, numerical simulations have shown that strongly shear-thinning polymer solutions (fluids with a shear viscosity that decreases with increasing flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 57 publications
4
65
0
Order By: Relevance
“…A constant spacing between particles is also beneficial for the real-time analysis of flowing cells since it reduces computational costs associated with data analysis [18]. Shear-thinning fluids display an almost flat velocity profile near the channel centerline at De > 1, thus flowing cells would potentially be undeformed (or only slightly deformed), which is optimal for manipulation of delicate cells [32]. Furthermore, as compared to inertial microfluidics, the relatively low flow rates needed to achieve ordering are more compatible with downstream droplet generation systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A constant spacing between particles is also beneficial for the real-time analysis of flowing cells since it reduces computational costs associated with data analysis [18]. Shear-thinning fluids display an almost flat velocity profile near the channel centerline at De > 1, thus flowing cells would potentially be undeformed (or only slightly deformed), which is optimal for manipulation of delicate cells [32]. Furthermore, as compared to inertial microfluidics, the relatively low flow rates needed to achieve ordering are more compatible with downstream droplet generation systems.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be emphasised that shear-thinning liquids have always been considered as detrimental for particle alignment, since particles tend to migrate towards the channel walls [30,31]. Only very recently, Del Giudice et al [32] showed that moving particles can be aligned on the centreline of a straight squareshaped microchannel, even in a shear-thinning liquid, by increasing the ratio of the particle size to the channel height. Therefore, further investigation on viscoelastic particle ordering seems at order.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [21]). Since in such non-Newtonian liquids shear thinning, leading to a non-constant viscosity, comes often simultaneously into play with a fluid elasticity, the specific contribution of a non-constant viscosity to particle CSM is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Particle focusing methods have been further characterized in detail in other studies. Particle motion was, in particular, investigated via shear‐thinning VEF flows where the lateral migration of particles was characterized accordingly (Del Giudice, D'Avino, Greco, Netti, & Maffettone, ; Del Giudice, Sathish, D'Avino, & Shen, ; Li, McKinley, & Ardekani, ; Lim, Nam, & Shin, ; Villone, D'Avino, Hulsen, Greco, & Maffettone, ). Individual and combined effects of fluid inertia, elasticity, and shear thinning on particle focusing were studied by Li and Xuan ().…”
Section: Passive Manipulation Of Particles In Vefs Flowmentioning
confidence: 99%